Understanding the strength softening of Zr/Mo and Zr/Ti nanostructured multilayers. (November 2019) - Wu, S.H.; Hou, Z.Q.; Zhang, J.Y.; Wang, Y.Q.; Wu, K.; Liu, G.; Sun, J.
Abstract: Zr/Mo and Zr/Ti nanostructured multilayers manifest a peak hardness at the critical layer thickness of ~10 and ~20 nm, respectively. The non-monotonical thickness-dependent hardness is understood in terms of the back stress, which is closely correlated with the dislocation absorption probability by the interfaces. It appears that strength softening occurs as gliding dislocations can be absorbed by interfaces at smaller layer thickness. Furthermore, incoherent interface in the Zr/Mo with discontinuous slip systems is more effective to block dislocation motion than the Zr/Ti with continuous ones, resulting in a higher dislocation storage ability. Graphical abstract: Unlabelled Image